The Retina as a Surrogate Marker for Pediatric Cerebral Malaria - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators from Malawi-Liverpool-Wellcome Trust Research Program, Malawi; University of Liverpool, UK; Michigan State University, USA; Vancouver General Hospital, Canada; and Ophthalmology Centers in Edinburgh, UK, review the evidence for associations between retina and brain neurovasculature, and the extent to which malarial retinopathy reflects cerebrovascular damage.